Self-efficacy, planning and action control in an oral self-care intervention - Zhou, G.; Sun, C.; Knoll, N.; Hamilton, Kyra; Schwarzer, R. (Oxford University Press, 2015)
© The Author 2015. Published by Oxford University Press. All rights reserved. To evaluate a theory-guided intervention on oral self-care and examine the possible mechanisms among self-regulatory factors, two brief intervention arms were compared, an information-based education treatment and a self-regulation treatment focusing on planning and action control. Young adults (N = 284; aged 18-29 years) were assessed at baseline and 1 month later. The self-regulation intervention improved levels of oral self-care, dental planning and action control. Moreover, a moderated mediation model with planning as the mediator between experimental conditions and dental outcome, and self-efficacy as well as action control as moderators elucidated the mechanism of change. More self-efficacious participants in the self-regulation condition benefitted in terms of more planning, and those who monitored their actions yielded higher levels of oral hygiene. Dental self-efficacy, dental planning and action control are involved in the improvement of oral self-care. Their joint consideration may contribute to a better understanding of health behavior change.